Spain - Skorupska, Adriana (The Role of Regions in EU-China Relations, 2021)
One objective of this chapter is to characterize the activities between Spanish communities and Chinese provinces and cities – their intensity, scope, advantages and obstacles that they face. The question relates to a broader perspective – the bilateral state government relations and the EU-China cooperation: is there any correlation between the relations at the state level and the regional level? Moreover, one of the ultimate goals of the whole project is to analyse the impact of the EU-China relations on paradiplomacy. Do the autonomous communities see any role of the EU in their activities with Chinese partners? Do they need any support from the European Union to have more intense or effective cooperation with this Asian partner?